(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The review of the literature provides information on changes in vascular-platelet hemostasis, platelet count, disorders of adhesion and aggregation properties, hemorrhagic complications in chronic liver disease. The results of the study of vascular-platelet hemostasis in patients with chronic liver diffuse disease were analyzed.